Integrated Landslide Mitigation Model in Physics Concept of Environmental Pollution and Alternative Energy - Maulana, Yudi; Shabrina, Annida Nurul; Karyadi, Bhakti (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This research integrates landslide disaster mitigation into physics education, with a focus on environmental pollution and alternative energy for high school students. The research aims to address the frequent landslides in Indonesia, particularly in Central Bengkulu Regency, which can cause significant disruptions. The objective is to develop a model for integrating disaster mitigation into physics education at MAN Insan Cendekia Central Bengkulu. The research method employed is Research and Development (R&D) using the 4D model, limited to the design stage. The research subjects were students in class XI-1 specializing in Physics at MAN Insan Cendekia. The analysis of disaster potential in Central Bengkulu indicates a need for disaster mitigation education. The Butterfly Webbed Concept Map was developed to integrate physics material with disaster mitigation education. It provides a visual representation of the relationship between environmental pollution, alternative energy, resource utilization, and landslide disaster mitigation. This integration can be applied in physics learning for disaster risk awareness for students.